Prescribing Pattern of Vitamins in Dermatologic Disorders at Tertiary Care Teaching Hospital in Western India - Patel, Zankrut J.; Prajapati, Akanksha; Thaker, Vidhi; Patel, Sumit (Universitas Padjadjaran, Indonesia, 2023)
Skin ailments are a major burden in society. It is thought that Vitamins may help in improving skin health and appearance, but their deficiency may cause disease. The data regarding vitamin usage patterns in dermatologic practice in India is lacking. Therefore, the present study has been planned to analyze the prescribing pattern of vitamins. A cross-sectional, observational study was carried out at the outpatient department of dermatology at GCSMCH and RC, Ahmedabad, for 12 months from October 2019 to September 2020. Prescriptions of 500 patients were analyzed for common skin conditions and prescribing patterns. All the data were compiled into Microsoft Office Excel, and a descriptive statistical analysis was conducted. Out of 500 patients, males and females were 226(45%) and 274 (55%), respectively. Most of them had skin appendage-related diseases (28%). Out of the total of 1935 prescribed drugs, 619(31.98%) vitamins were prescribed in 500 patients with an average of 1.23 per prescription, in which the majority of drugs were as fixed-dose combination (FDC). Of 1211 prescribed vitamins, vitamin A was the most commonly prescribed vitamin 197 (39.4%). There is no association between prescribed vitamins and the prevalence of diseases. (p>0.05). However, the P-value is highly significant, suggesting an association between prescribed vitamins and different age groups. (p<0.05). Skin appendage-related diseases are commonest skin ailments. The use of vitamins in skin conditions is very common, particularly in oral formulations, among which the majority were prescribed as FDCs.